A comparative study on the effect of glazing and cooling for compound parabolic concentrator PV systems – Experimental and analytical investigations. (1st December 2016) - Bahaidarah, Haitham M.; Gandhidasan, P.; Baloch, Ahmer A.B.; Tanweer, Bilal; Mahmood, M.
Graphical abstract: Highlights: We model glazed and unglazed PV-CPC systems with and without active water cooling. Model is validated with experimental results and found good agreement. Significant increase in the maximum power output is observed with active cooling. Unglazed PV-CPC system is recommended for greater electric power output. Levelized cost of energy found was found lower for unglazed CPC with cooling. Abstract: A key barrier to achieving the economic viability and widespread adoption of photovoltaic (PV) technology for the direct conversion of solar radiation to electricity is the losses related to the high operating temperatures of typical flat-type PV modules. This technical and economic study addresses the cost reduction of PV systems by proposing a methodology for the improvement of solar cell efficiency using low-concentration PV technology and compound parabolic concentrators (CPCs). A theoretical model was developed to evaluate the performance of PV-CPC systems considering their optical, thermal and electrical properties. The model was implemented to investigate glazed and unglazed PV-CPC systems with and without active cooling and it was validated against experimental data. A laboratory-scale bench-top PV string was designed and built with symmetrically truncated CPC modules in these four configurations. The constructed glazed and unglazed PV-CPC systems were used for measurements at the geographic location of Dhahran and showed a very good agreement of 3.8–6.5% between the calculated and experimental results. The effect of glazing was studied and from the electrical point of view, glazing was found to reduce the power output. From the thermal point of view, glazing increased the thermal gain of the PV-CPC system. An unglazed PV-CPC system is recommended for greater electric power output, and glazed system is recommended for higher thermal gain. For economic feasibility, levelized cost of energy (LCE) analysis was performed using annual power output simulations and cost parameters incurred in the installation and operations phase of four systems considered. Annual power output was found to increase by 53.45% for unglazed CPC and 37.1% for glazed CPC systems. The minimum LCE of 0.84 (€/kW h) was found for unglazed CPC with cooling whereas the maximum LCE of 1.67(€/kW h) was obtained for glazed uncooled system due to high cell temperatures.